The Effect of Melatonin on Thrombosis, Sepsis and Mortality Rate in COVID-19 Patients - Zainab Thanon Hasan (Elsevier, 2022)
Objectives: This study aimed to determine the effect of melatonin on thrombosis, sepsis, and mortality rate in adult patients with severe coronavirus infection (COVID-19). Methods: This single-center, prospective, randomized clinical trial was conducted from 1 December 2020 to 1 June 2021 at Al-Shifaa hospital in Mosul, Iraq. There were 158 patients with severe COVID-19 included in the study: 82 in the melatonin group (who received 10 mg melatonin in addition to standard therapeutic care) and 76 in the control group (given standard therapeutic care only). Patients were chosen by a blocked randomization design. The physician then evaluated and recorded the incidence of thrombosis, sepsis, and mortality rate on days 5, 11, and 17 of symptoms. Results: The intervention group consisted of 82 patients, while the control group consisted of 76 patients. In comparison to the control group, thrombosis and sepsis developed significantly less frequently (P < 0.05) in the melatonin group during the second week of infection, while mortality was significantly higher in the control group (P < 0.05). Conclusions: Adjuvant use of melatonin may help to reduce thrombosis, sepsis, and mortality in COVID-19 patients.